2x+1=9
Your going to always try to leave the x variable alone.
2x+1=9
-1 -1
2x=8
/2 /2
x=4
Answer:
8x+6y=48
x+y=7
multiply bottom equation by 6:
8x+6y=48
6x+6y=42
subtract equations:
2x=6
divide 6 by 2:
x=3
therefore:
y=4
Answer:
n°
Step-by-step explanation:
Your selection is correct. Once again, they are alternate angles, meaning they're equal to one another.
I assume you mean:
[x^(5/6)]/[x^(1/6)]
The rule for dividing similar bases with different exponents is:
(a^b)/(a^c)=a^(b-c)
In this case we have:
x^(5/6-1/6)
x^(4/6)
x^(2/3)